Effect of Si3N4‐Mediated Inversion Layer on the Electroluminescence Properties of Silicon Nanocrystal Superlattices. (22nd March 2018) - López‐Vidrier, Julian; Gutsch, Sebastian; Blázquez, Oriol; Valenta, Jan; Hiller, Daniel; Laube, Jan; Blanco‐Portals, Javier; López‐Conesa, Lluís; Estradé, Sònia; Peiró, Francesca; Garrido, Blas; Hernández, Sergi; et al.
Abstract: The achievement of an efficient all‐Si electrically‐pumped light emitter is a major milestone in present optoelectronics still to be fulfilled. Silicon nanocrystals (Si NCs) are an attractive material which, by means of the quantum confinement effect, allow attaining engineered bandgap visible emission from Si by controlling the NC size. In this work, SiO2 ‐embedded Si NCs are employed as an active layer within a light‐emitting device structure. It is demonstrated that the use of an additional thin Si3 N4 interlayer within the metal–insulator–semiconductor device design induces an enhanced minority carrier injection from the substrate, which in turn increases the efficiency of sequential carrier injection under pulsed electrical excitation. This results in a substantial increase in the electroluminescence efficiency of the device. Here, the effect of this Si3 N4 interlayer on the structural, optical, electrical, and electro‐optical properties of a Si NC‐based light emitter is reported, and the physics underlying these results is discussed. Abstract : In this work, an additional 2‐nm‐thick Si3 N4 interlayer has been included within metal‐insulator‐semiconductor devices containing Si nanocrystal (NC)‐based superlattices as emitter layer. It is demonstrated that this occurrence enhances the electroluminescence emission of the Si NCs under pulsed electrical excitation, which is explained in terms of the physics underlying the mechanism of sequential carrier injection into the NCs.